Utility of the central motor conduction time recorded from the abductor pollicis brevis and the abductor digiti minimi muscles in patients with C6–7 myelopathy. (4th March 2018) - Imajo, Yasuaki; Kanchiku, Tsukasa; Suzuki, Hidenori; Funaba, Masahiro; Nishida, Norihiro; Taguchi, Toshihiko
Abstract : Objective : Central motor conduction time (CMCT) recorded from the abductor pollicis brevis (CMCT-APB) and abductor digiti minimi (CMCT-ADM) muscles may enable the evaluation of patients with C6–7 myelopathy. CMCT is more useful for the evaluation of the function of spinal cord than magnetic resonance imaging (MRI) findings. CMCT may be associated with age and height. However, there are few reports regarding CMCT-APB in normal subjects. This study aimed to investigate the relationships between age, height, and conduction parameters in normal subjects to assess the effectiveness of using CMCT-APB and CMCT-ADM for the evaluation of patients with C6–7 and C7–T1 myelopathy. Design : Retrospective study. Methods : Fifteen patients with cervical compressive myelopathy at C6–7 (11 patients) or C7-T1 (4 patients) level were enrolled. The control group consisted of 150 normal subjects (mean age 45.8±17.0 years; mean height 163.6±8.9 cm). Motor evoked potentials induced by transcranial magnetic stimulation and F-waves were used to determine CMCT. Outcome measures : CMCT-APB, CMCT-ADM. Results : The normative values of CMCT-APB and CMCT-ADM were 5.3±0.7 ms and 5.2±0.8 ms, respectively. CMCT-APB was significantly longer than CMCT-ADM for patients with C6–7 myelopathy (P < 0.05). Neither of the CMCTs for those with C7–T1 myelopathy were significantly different from those of controls, but CMCT-APB was more prolonged than CMCT-ADM in patients with C6–C7 myelopathy. Conclusions : CMCTs improve the accuracy of the diagnosis of myelopathy by pinpointing the lesion in combination with MRI imaging. Selective CMCT-APB prolongation may be seen in patients with C6–7 myelopathy but not C7-T1 myelopathy.